Critical appraisal of clinical trials in multiple system atrophy: Toward better quality - Castro Caldas, Ana; Levin, Johannes; Djaldetti, Ruth; Rascol, Olivier; Wenning, Gregor; Ferreira, Joaquim J. (Movement disorders, 2017)
ABSTRACT Multiple system atrophy (MSA) is a rare neurodegenerative disease of undetermined cause. Although many clinical trials have been conducted, there is still no treatment that cures the disease or slows its progression. We sought to assess the clinical trials, methodology, and quality of reporting of clinical trails conducted in MSA patients. We conducted a systematic review of all trials with at least 1 MSA patient subject to any pharmacological/nonpharmacological interventions. Two independent reviewers evaluated the methodological characteristics and quality of reporting of trials. A total of 60 clinical trials were identified, including 1375 MSA patients. Of the trials, 51% (n = 31) were single‐arm studies. A total of 28% (n = 17) had a parallel design, half of which (n = 13) were placebo controlled. Of the studies, 8 (13.3%) were conducted in a multicenter setting, 3 of which were responsible for 49.3% (n = 678) of the total included MSA patients. The description of primary outcomes was unclear in 60% (n = 40) of trials. Only 10 (16.7%) clinical trials clearly described the randomization process. Blinding of the participants, personnel, and outcome assessments were at high risk of bias in the majority of studies. The number of dropouts/withdrawals was high (n = 326, 23.4% among the included patients). Overall, the design and quality of reporting of the reviewed studies is unsatisfactory. The most frequent clinical trials were small and single centered. Inadequate reporting was related to the information on the randomization process, sequence generation, allocation concealment, blinding of participants, and sample size calculations. Although improved during the recent years, methodological quality and trial design need to be optimized to generate more informative results. © 2017 International Parkinson and Movement Disorder Society